2016
DOI: 10.1155/2016/8737654
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sleep Timing, Sleep Duration, and Sleep Quality on Depressive Symptoms and Suicidal Ideation amongst Japanese Freshmen: The EQUSITE Study

Abstract: Aim. The aim of this study was to identify the impact of bedtime, wake time, sleep duration, sleep-onset latency, and sleep quality on depressive symptoms and suicidal ideation amongst Japanese freshmen. Methods. This cross-sectional data was derived from the baseline survey of the Enhancement of Q-University Students Intelligence (EQUSITE) study conducted from May to June, 2010. A total of 2,631 participants were recruited and completed the following self-reported questionnaires: the Pittsburgh Sleep Quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 38 publications
2
41
0
1
Order By: Relevance
“…Distinct sleep dimensions, other than duration, may more precisely capture influences that drive the association between sleep and obesity (Jarrin et al, 2013). Moreover, sleep quality has shown stronger associations with variables such as depression symptoms (Supartini et al, 2016), which appears to account, at least in part, for the relationship between weight and sleep quality (Sawyer et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distinct sleep dimensions, other than duration, may more precisely capture influences that drive the association between sleep and obesity (Jarrin et al, 2013). Moreover, sleep quality has shown stronger associations with variables such as depression symptoms (Supartini et al, 2016), which appears to account, at least in part, for the relationship between weight and sleep quality (Sawyer et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Sleep quality has been frequently used as a single indicator encompassing a collection of sleep measures, such as: total sleep time, sleep-onset latency, degree of fragmentation, total wake time, sleep efficiency, and sometimes sleep-disruptive events such as spontaneous arousals or apnea (Krystal and Edinger, 2008). Self-reported sleep quality is affected by gender and age; women and older people are more likely to report lower sleep quality and a higher number of sleep problems (Madrid-Valero et al, 2017; ª 2017 European Sleep Research Society Ohayon et al, 2004;Uhlig et al, 2014;Zhang and Wing, 2006), and it seems to be more closely associated to psychological distress than duration alone (Supartini et al, 2016). Sleep quality also appears to be related to BMI through an inverse relationship (Hung et al, 2013;Kim, 2015), although the opposite has also been reported (Gildner et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, early awakening to adapt to their social schedule (e.g., for attending classes early in the morning) consequently brings about insufficient sleep especially in evening-type students. Numerous studies have reported that either insufficient sleep or later chronotype is associated with deterioration of physical health, mental health [3][4][5] and health-related quality of life [6,7] as well as worse academic performance [8][9][10][11][12] in the young population.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that as high as 33-59% of university students have poor sleep quality, which is associated with their worsened health status and academic performance [5,[13][14][15][16][17][18][19]. In these previous studies, sleep quality was defined as "poor" or "good" using the Pittsburg Sleep Quality Index (PSQI), a widely used scale evaluating the following seven components: subjective sleep quality, sleep latency, sleep duration, habitual sleep efficiency, sleep disturbances, use of sleep medication, and daytime dysfunction [20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found variable rates of sleep disturbances in this population. The prevalence of sleep disturbances ranges from 3.0 to 74.2% worldwide, for instance, 3.0% in Thailand (Mohammadbeigi et al ., ), 9.8% in Lebanon (Younes et al ., ), 22.5% in the USA (Gress et al ., ), 33.3% in Japan (Supartini et al ., ), 74.2% in Saudi Arabia (Siddiqui et al ., ), 51.8% in Chile (Velez et al ., ), and 61.7% in Iran (Mohammadbeigi et al ., ). Apart from different sampling methods and geographic locations, the use of different instruments, such as the PSQI (Mohammadbeigi et al ., ), the Insomnia Severity Index (ISI; Gress et al ., ) and non‐quantitative measures (Peltzer and Pengpid, ) could account for such variation in prevalence.…”
Section: Introductionmentioning
confidence: 99%